Electrokinetic Proton Transport in Triple (H+/O2−/e−) Conducting Oxides as a Key Descriptor for Highly Efficient Protonic Ceramic Fuel Cells. Issue 11 (25th March 2021) - Seong, Arim; Kim, Junyoung; Jeong, Donghwi; Sengodan, Sivaprakash; Liu, Meilin; Choi, Sihyuk; Kim, Guntae
Abstract: Recently, triple (H + /O 2− /e − ) conducting oxides (TCOs) have shown tremendous potential to improve the performance of various types of energy conversion and storage applications. The systematic understanding of the TCO is limited by the difficulty of properly identifying the proton movement in the TCO. Herein, the isotope exchange diffusion profile (IEDP) method is employed via time‐of‐flight secondary ion mass spectrometry to evaluate kinetic properties of proton in the layered perovskite‐type TCOs, PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5+ δ (PBSCF).Within the strategy, the PBSCF shows two orders of magnitude higher proton tracer diffusion coefficient ( D * H, 1.04 × 10 −6 cm 2 s −1 at 550 °C) than its oxygen tracer diffusion coefficient at even higher temperature range ( D * O, 1.9 × 10 −8 cm 2 s −1 at 590 °C). Also, the surface exchange coefficient of a proton ( k *H ) is successfully obtained in the value of 2.60 × 10 −7 cm s −1 at 550 °C. In this research, an innovative way is provided to quantify the proton kinetic properties ( D * H and k *H ) of TCOs being a crucial indicator for characterizing the electrochemical behavior of proton and the mechanism of electrode reactions. Abstract : Triple (H + /O 2− /e − ) conducting oxides (TCOs) have shown tremendous potential to improve the performance of various energy conversion and storage applications. However, the direct visualization of proton movement has not been investigated. Herein, the isotope exchange diffusion profile method is employed to evaluate proton kinetic properties ( D * H and k * H ) in TCOs being crucial indicator for highly efficient protonic ceramic fuel cells.